Travel and Identity: Studies in Literature, Culture and Language (Issues in Literature and Culture,, 2018)
This book presents a selection of research papers dealing with the notions of travel and identity in Anglophone literature and culture. Collectively, the chapters ponder such notions as self and other, race, centre and periphery, thus shedding new light on a number of issues that are highly relevant in the context of the ongoing migration crisis. The contributors employ a diverse range of theoretical standpoints - from close reading to deconstruction, from historically informed approaches to linguistic analysis - and thus offer a nuanced panorama of these issues, especially from the nineteenth century onwards.